2017
DOI: 10.1083/jcb.201611027
|View full text |Cite
|
Sign up to set email alerts
|

Rab2 promotes autophagic and endocytic lysosomal degradation

Abstract: Rab7 promotes fusion of autophagosomes and late endosomes with lysosomes. Lőrincz et al. show that Rab2 is critical for the delivery of autophagic and endocytic cargo to lysosomes and for their degradation, and that it promotes autophagosome–lysosome fusion. The results suggest Rab2 and Rab7 coordinately promote autophagic and endosomal degradation and lysosome function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
141
0
9

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 118 publications
(158 citation statements)
references
References 38 publications
8
141
0
9
Order By: Relevance
“…While this work was in revision, two papers have been published describing the role of Rab2 in LE-lysosome fusion and autophagosome-lysosome fusion, respectively [79,89]. Lőrincz et al use Drosophila garland cells and fat bodies and human cells to essentially show the same requirement for Rab2 in LE-lysosome fusion and autophagy described here [79].…”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…While this work was in revision, two papers have been published describing the role of Rab2 in LE-lysosome fusion and autophagosome-lysosome fusion, respectively [79,89]. Lőrincz et al use Drosophila garland cells and fat bodies and human cells to essentially show the same requirement for Rab2 in LE-lysosome fusion and autophagy described here [79].…”
Section: Discussionmentioning
confidence: 94%
“…In Gie e00336 /Df cells, GFP-Rab2 was strongly recruited to the limiting membranes of many of the enlarged late endosomal vacuoles (Figure 10(a)), demonstrating that it does not reach LEs through fusion with lysosomal compartments. It has been suggested that Rab2 arrives to LEs on Golgi-derived vesicles in a HOPS-mediated fusion event and is subsequently quickly released from the membrane [48,79]. Surprisingly, we found that in both Vps39 Δ1 /Df and lt 11 /Df garland cells GFP-Rab2 was still present on the membranes of many of the 2-h tracer-positive and negative enlarged late endosomal vacuoles (Figure 10(a)).
10.1080/15548627.2018.1458170-F0010Figure 10.Location of Rab2 in HOPS component and Gie / Arl8 mutants and schematic representation of the function of Rab2 in the endolysosomal system.
…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations